A Comparative Analysis of Children’s Learning Motivation Between Conventional Literacy Learning and a Learning-by-Doing Approach in a Community Literacy Program - Putri Kiki Sushella; Sardin Sardin; Yanti Shantini; Riska Trinanda (Universal Education Jurnal Teaching and Learning, 2026)
Children’s literacy development in non-formal educational settings is influenced not only by access to reading materials but also by learners’ motivation to participate in literacy activities. In many community literacy programs, learning practices are often limited to access-based approaches that emphasize reading exposure with relatively limited opportunities for active participation. Such conditions may affect children’s engagement and motivation in literacy activities. This study aims to conduct a comparative analysis of children’s learning motivation between conventional literacy learning and a learning-by-doing approach implemented at Teras Baca Taman Gantung, a community-based literacy program. This study employed a qualitative descriptive design with a comparative perspective. The participants consisted of four primary school–aged children who regularly attended literacy activities in the program. Data were collected through attendance documentation, direct observation of students’ learning behaviors, and semi-structured interviews. Observational data were coded to identify behavioral patterns related to learning motivation, including off-task behavior, passive participation, and active engagement. The findings indicate that students demonstrated lower learning motivation during conventional literacy activities, reflected in irregular attendance and off-task behaviors. In contrast, the learning-by-doing approach was associated with higher levels of participation and more active engagement during literacy sessions. These findings highlight the importance of participatory learning environments in supporting children’s engagement in community literacy initiatives. The results suggest that experiential learning activities can foster stronger learning motivation in community-based literacy programs.